9514 1404 393
Explanation:
Definition
The determinant of a square matrix is a single number that is computed (recursively) as the sum of products of the elements of a row or column and the determinants of their cofactors. The determinant of a single element is the value of that element.
The cofactor of an element in an n by n matrix is the (n-1) by (n-1) matrix that results when the row and column of that element are deleted. The "appropriate sign" of the element is applied to the cofactor matrix. The "appropriate sign" of an element is positive if the sum of its row and column numbers is even, negative otherwise. (Rows and columns are considered to be numbered 1 to n in an n by n matrix.)
Uses
The inverse of a square matrix is the transpose of the cofactor matrix, divided by the determinant. Hence if the determinant is zero, the inverse matrix is undefined. This means any system of equations the matrix might represent will have no distinct solution. (There may be zero solutions, or there may be an infinite number of solutions. The determinant by itself cannot tell you which.)
Cramer's Rule for the solution of linear systems of equations specifies that the value of any given variable is the ratio of the determinants of two matrices. The numerator matrix is the original matrix with the coefficients of the variable replaced by the constants in the standard-form equations; the denominator matrix is the original coefficient matrix. This rule lets you solve a system of 3 equations in 3 variables by computing 3+1 = 4 determinants, for example.
Let's look at an example.
If we wanted to solve this system of equations
[tex]\begin{cases}2x-y = 2\\x+y = 7\end{cases}[/tex]
Then it's equivalent to solving this matrix equation
[tex]\begin{bmatrix}2 & -1\\1 & 1\end{bmatrix}\begin{bmatrix}x\\y\end{bmatrix}=\begin{bmatrix}2\\7\end{bmatrix}[/tex]
We can then further condense that into the form
[tex]Aw = B[/tex]
Where,
[tex]A = \begin{bmatrix}2 & -1\\1 & 1\end{bmatrix}\\\\w = \begin{bmatrix}x\\y\end{bmatrix}\\\\B = \begin{bmatrix}2\\7\end{bmatrix}[/tex]
------------------------------------------
To solve the matrix equation Aw = B, we could compute the inverse matrix [tex]A^{-1}[/tex] and left-multiply both sides by this to isolate w.
So we'd go from [tex]Aw=B[/tex] to [tex]w = A^{-1}*B[/tex]. The order of multiplication is important.
For any 2x2 matrix of the form
[tex]P = \begin{bmatrix}a & b\\c & d\end{bmatrix}[/tex]
its inverse is
[tex]P^{-1} = \frac{1}{ad-bc}\begin{bmatrix}d & -b\\-c & a\end{bmatrix}[/tex]
Notice the expression ad-bc in the denominator of that fractional term outside. This [tex]ad-bc[/tex] expression represents the determinant of matrix P. Some books may use the notation "det" to mean "determinant"
[tex]P^{-1} = \frac{1}{\det(P)}\begin{bmatrix}d & -b\\-c & a\end{bmatrix}[/tex]
or you may see it written as
[tex]P^{-1} = \frac{1}{|P|}\begin{bmatrix}d & -b\\-c & a\end{bmatrix}[/tex]
Those aren't absolute value bars, even if they may look like it.
Based on that, we can see that the determinant must be nonzero in order to compute the inverse of the matrix. Consequently, the determinant must be nonzero in order for Aw = B to have one solution.
If the determinant is 0, then we have two possibilities:
There are infinitely many solutions (aka the system is dependent)There are no solutions (the system is inconsistent)So a zero determinant would have to be investigated further as to which outcome would occur.
------------------------------------------
Let's return to the example and compute the inverse (if possible).
[tex]A = \begin{bmatrix}2 & -1\\1 & 1\end{bmatrix}\\\\A^{-1} = \frac{1}{2*1 - (-1)*1}\begin{bmatrix}1 & 1\\-1 & 2\end{bmatrix}\\\\A^{-1} = \frac{1}{3}\begin{bmatrix}1 & 1\\-1 & 2\end{bmatrix}\\\\[/tex]
In this case, the inverse does exist.
This further leads to
[tex]w = A^{-1}*B\\\\w = \frac{1}{3}\begin{bmatrix}1 & 1\\-1 & 2\end{bmatrix}*\begin{bmatrix}2\\7\end{bmatrix}\\\\w = \frac{1}{3}\begin{bmatrix}1*2+1*7\\-1*2+2*7\end{bmatrix}\\\\w = \frac{1}{3}\begin{bmatrix}9\\12\end{bmatrix}\\\\w = \begin{bmatrix}(1/3)*9\\(1/3)*12\end{bmatrix}\\\\w = \begin{bmatrix}3\\4\end{bmatrix}\\\\\begin{bmatrix}x\\y\end{bmatrix} = \begin{bmatrix}3\\4\end{bmatrix}\\\\[/tex]
This shows that the solution is (x,y) = (3,4).
As the other person pointed out, you could use Cramer's Rule to solve this system. Cramer's Rule will involve using determinants and you'll be dividing over determinants. So this is another reason why we cannot have a zero determinant.
Consider the functions f and g in the tables below. f(x) = 90x2 + 180x + 92 x y 0 92 1 362 2 812 3 1,442 4 2,252 5 3,242 g(x) = 6x x y 0 1 1 6 2 36 3 216 4 1,296 5 7,776 Which of the following statements is true? A. At approximately x = 4.39, the rate of change of f is equal to the rate of change of g. B. As x increases, the rate of change of g exceeds the rate of change of f. C. As x increases, the rate of change of f exceeds the rate of change of g. D. For every value of x, the rate of change of g exceeds the rate of change of f.
Answer:
As x increases, the rate of change of g exceeds the rate of change of f.
Step-by-step explanation:
Given
[tex]f(x) = 90x^2 + 180x + 92[/tex]
[tex]\begin{array}{ccccccc}x & {0} & {1} & {2} & {3} & {4} & {5} & f(x) & {92} & {362} & {812} & {1442} & {2252} & {3242} \ \end{array}[/tex]
[tex]g(x) = 6^x[/tex]
[tex]\begin{array}{ccccccc}x & {0} & {1} & {2} & {3} & {4} & {5} & g(x) & {1} & {6} & {36} & {216} & {1296} & {7776} \ \end{array}[/tex]
Required
Which of the options is true?
A. At [tex]x \approx 4.39[/tex], f(x) has the same rate of change as g(x)
Rate of change is calculated as:
[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
For f(x)
[tex]f(x) = 90x^2 + 180x + 92[/tex]
[tex]f(4.39) = 90*4.39^2 + 180*4.39 + 92 = 2616.689[/tex]
So, the rate of change is:
[tex]m = \frac{2616.689}{4.39} = 596.06[/tex]
For g(x)
[tex]g(x) = 6^x[/tex]
[tex]g(4.39) = 6^{4.39} = 2606.66[/tex]
So, the rate of change is:
[tex]m = \frac{2606.66}{4.39} = 593.77[/tex]
The rate of change of both functions are not equal at x = 4.39. Hence, (a) is false.
B. Rate of change of g(x) is greater than f(x) with increment in x
Using the formula in (a), we have:
[tex]\begin{array}{ccccccc}x & {0} & {1} & {2} & {3} & {4} & {5} & f(x) & {92} & {362} & {812} & {1442} & {2252} & {3242} & m &\infty & 362 & 406 & 480 & 563 &648.4\ \end{array}[/tex]
[tex]\begin{array}{ccccccc}x & {0} & {1} & {2} & {3} & {4} & {5} & g(x) & {1} & {6} & {36} & {216} & {1296} & {7776} & m & \infty & 6 & 18 & 72 & 324 & 1555 \ \end{array}[/tex]
From x = 1 to 4, the rate of change of f is greater than the rate of g.
However, from x = 5, the rate of change of g is greater than the rate of f.
This means that (b) is true.
The above table further shows that (c) and (d) are false.
Answer:
Step-by-step explanation:
C
3.
Steve went to buy clothes for his school uniform. He bought five shirts that each cost the same
amount and one school jacket costing $20. The items he bought cost a total of $95 before tax was
added. What was the cost of each shirt?
Cost of jacket = $20
No. Of jackets = 1
Let the cost of shirt be x
No of shirts = 5
ATQ
5x + 1(20) = 95
5x + 20 = 95
5x = 95 - 20
5x = 75
x = 75/5
x = 15
Therefore cost of each shirt was $15
Answered by Gauthmath must click thanks and mark brainliest
In the figure, angle D measures 127° and angle A measures 75°.
Complete the equation to solve for b, the measurement of angle B.
Angles C and D are supplementary, or they add up to 180.
b = 180 - 75 - (180 - 127)
Hope this helps!
Answer:
Step-by-step explanation:
∠C + ∠D = 180 {Linear pair}
∠C + 127 = 180
∠C = 180 - 127
In ΔABC ,
∠A + ∠B + ∠C = 180 {angle sum property of triangle}
∠B = 180 - ∠A - ∠C
b = 180 - 75 - (180 - 127)
4
5
7
11
19
?
a. 41
b. 35
c. 23
d. 29
Answer:
35
Step-by-step explanation:
The pattern is adding powers of 2.
4+1=5 (exception)
5+2=7
7+4=11
11+8=19
19+16=35
Answer:
35
Step-by-step explanation:
4 + 1 = 5
5 + (1 × 2) = 5 +2 =7
7 + (2×2) = 7 + 4 = 11
11 +(4×2) = 11 + 8 = 19
19 + (8×2) = 19 + 16 = 35
A process manufactures ball bearings with diameters that are normally distributed with mean 25.1 millimeters and standard deviation 0.08 millimeter. (a) [5pts] What proportions of the diameters are greater than 25.4
Answer:
The proportions of the diameters that are greater than 25.4 millimeters is 5%.
Step-by-step explanation:
Given;
mean of the normal distribution, m = 25.1 millimeters
standard deviation, d = 0.08 millimeter
1 standard deviation above the mean = m + d = 25.1 + 0.08 = 25.18
2 standard deviation above mean = m + 2d = 25.1 + 2(0.08) = 25.26
3 standard deviation above the mean = m + 3d = 25.1 + 3(0.08) = 25.34
4 standard deviation above the mean = m + 4d = 25.1 + 4(0.08) = 25.42
To obtain a diameter greater than 25.4, we select data after 4 standard deviation above the mean.
Data within 4 standard deviation above the mean is 95%
Data outside 4 standard deviation above the mean is 5%
Therefore, the proportions of the diameters that are greater than 25.4 millimeters is 5%.
solve similar triangles (advanced)
solve for x
Answer:
27/2 =x
Step-by-step explanation:
We can write a ratio to solve
3 2
----- = ---------
3+x 11
Using cross products
3*11 = 2(3+x)
33 = 6+2x
Subtract 6 from each side
33-6 = 6+2x-6
27 = 2x
27/2 = 2x/2
27/2 =x
If Y / 4 - 12 = 3.5, what is the value of y?
Can someone do #8 #9 & #10 for me please?!❤️
Answer:
8. 72% × 850
= 72/100 × 850
= 72 × 8,5
= 612 ( b )
9. Poin B = 4 ( b )
Answer:
8. B
9. B
10. C
Step-by-step explanation:
8. To find 72% of 850, you would multiply 0.72 x 850. When you do that, it gives you 612.
9. B is on the number 4.
10. The expression is asking, "What is the absolute value of 28?". Absolute value means that the number inside will always be positive. For example, if it was -28, the absolute value would turn to 28. Since the question has 28 already positive, there is no change, so the answer would be 28.
Find a homogeneous second-order Cauchy-Euler equation with real coefficients if the given number is a root of its auxiliary equation.
mi= i
C1cos(ln(x)) + C2sin(ln(x))
I'm going to assume that you mean to say that i = √(-1) is a root of the auxiliary equation. That is, if the Cauchy-Euler DE is
x ²y'' + axy' + by = 0
then the auxiliary equation obtained by substituting y = xᵐ is
x ² (m (m - 1) xᵐ ⁻ ²) + ax (m xᵐ ⁻ ¹) + bxᵐ = 0
which reduces to
m (m - 1) + am + b = 0
or
m ² + (a - 1) m + b = 0
By the fundamental theorem of algebra, we can write the quadratic in terms of its roots r₁ and r₂,
(m - r₁) (m - r₂) = 0
Given that one root is the imaginary unit i, and the coefficients of the aux. equation are real, it follows that the other root is -i, because complex roots must occur with their conjugates. So we have as our aux. equation,
(m - i ) (m + i ) = 0
or
m ² + 1 = 0
Then a - 1 = 0 and b = 1, so that the given root and general solution correspond to the DE,
x ²y'' + xy' + y = 0
find the missing side lengths
Answer:
x=2
y=1.732
Step-by-step explanation:
we use the formulae.....
SOHCAHTOA
where..Cos 60°=1/x
cos60=0.5
0.5=1/1
X=2
0.8660=y/2
y= 1.732
A random sample of 200 people was taken. 90 of the people in the sample favored Candidate A. We are interested in determining whether or not the proportion of the population in favor of Candidate A is significantly more than 40%. The test statistic is a.1.44. b.1.25. c..95. d..80.
Answer:
a. 1.44
Step-by-step explanation:
We are interested in determining whether or not the proportion of the population in favor of Candidate A is significantly more than 40%.
At the null hypothesis, it is tested if the proportion is of at most 40%, that is:
[tex]H_0: p \leq 0.4[/tex]
At the alternative hypothesis, it is tested if the proportion is of more than 40%, that is:
[tex]H_1: p > 0.4[/tex]
The test statistic is:
[tex]z = \frac{X - \mu}{\frac{\sigma}{\sqrt{n}}}[/tex]
In which X is the sample mean, [tex]\mu[/tex] is the value tested at the null hypothesis, [tex]\sigma[/tex] is the standard deviation and n is the size of the sample.
0.4 is tested at the null hypothesis:
This means that [tex]p = 0.4, \sigma = \sqrt{0.4*0.6}[/tex]
A random sample of 200 people was taken. 90 of the people in the sample favored Candidate A.
This means that:
[tex]n = 200, X = \frac{90}{200} = 0.45[/tex]
Value of the test statistic:
[tex]z = \frac{X - \mu}{\frac{\sigma}{\sqrt{n}}}[/tex]
[tex]z = \frac{0.45 - 0.4}{\frac{\sqrt{0.4*0.6}}{\sqrt{200}}}[/tex]
[tex]z = 1.44[/tex]
Thus the correct answer is given by option a.
I need to know this answe ASAP
Answer:
look at the value of f(x) carefully when we put 7 from x the x take 2 value
Step-by-step explanation:
And g(x) function take 4 value. please look at the first option it has extra 2 so 2 plus 2 equal to 4 this means that the answer might be A. But look at D option it multiply by 2 so D option might be correct answer but we need some info and I want to continue. When I put 1 from x f(x)=1 and g(x)= 2 but when we look at the first option it is 1+2 equal to 3 but it must be 2 so the correct answer is not A and the correct answer is D
Which graph shows the solution to the system of linear inequalities?
x - 4y< 4
-
Y
Please help ASAP
Answer:
b
Step-by-step explanation:
i had it
Mary spent $4 more than 1/8 of her original amount of money on a bag. She then
Spent $12 more than 2/3 of her remaining money on groceries.Given that Mary had $24 left,how much did the bag cost?
Answer:
464 $
Step-by-step explanation:
Click on the graph where a transformation occurred that doesn't preserve the physical characteristics of rectangle FGHI.
Answer:
Click the graph in Quadrant 1
Step-by-step explanation:
This graph is bigger in side length.
Please help 20 points. I will give Brainly to who ever get it right.
Answer:
Step-by-step explanation:
(-∞,2)
Si una mujer gana más que su marido
Answer:
nada está bien gana bien.
A call center receives 25 callers per minute on average. On average, a caller spends 1 minute on hold and 4 minutes talking to a service representative. On average, how many callers are "in" the call center
Answer:
"125 callers" is the right answer.
Step-by-step explanation:
Given values:
Arrival calls rate,
= 25 per minute
Talking time,
= 4 minutes
Hold time,
= 1 minute
The flow time will be:
= [tex]1 \ minute \ + 4 \ minutes[/tex]
= [tex]5 \ minutes[/tex]
Flow rate,
= [tex]Arrival \ calls \ rate[/tex]
= [tex]25 \ per \ minute[/tex]
By using the Little's law,
⇒ [tex]WIP = Flow \ rate\times Flow \ time[/tex]
By substituting the values, we get
[tex]= 25\times 5[/tex]
[tex]=125[/tex]
Thus the above is the correct approach.
PLEASE HELPPPPPPPPPPPPPP
Answer:
False
Step-by-step explanation:
To find the inverse of a function, switch the variables and solve for y.
The inverse of f(n)=-(n+1)^3:
[tex]y=-(n+1)^3[/tex]
[tex]n=-(y+1)^3[/tex]
[tex]\sqrt[3]{n} =-(y+1)[/tex]
[tex]\sqrt[3]{n} =-y-1[/tex]
[tex]\sqrt[3]{n} +1=-y[/tex][tex]-(\sqrt[3]{n} +1)=y[/tex]
[tex]-\sqrt[3]{n} -1=y[/tex]
Answer:
False
Step-by-step explanation:
use undetermined coefficient to determine the solution of:y"-3y'+2y=2x+ex+2xex+4e3x
First check the characteristic solution: the characteristic equation for this DE is
r ² - 3r + 2 = (r - 2) (r - 1) = 0
with roots r = 2 and r = 1, so the characteristic solution is
y (char.) = C₁ exp(2x) + C₂ exp(x)
For the ansatz particular solution, we might first try
y (part.) = (ax + b) + (cx + d) exp(x) + e exp(3x)
where ax + b corresponds to the 2x term on the right side, (cx + d) exp(x) corresponds to (1 + 2x) exp(x), and e exp(3x) corresponds to 4 exp(3x).
However, exp(x) is already accounted for in the characteristic solution, we multiply the second group by x :
y (part.) = (ax + b) + (cx ² + dx) exp(x) + e exp(3x)
Now take the derivatives of y (part.), substitute them into the DE, and solve for the coefficients.
y' (part.) = a + (2cx + d) exp(x) + (cx ² + dx) exp(x) + 3e exp(3x)
… = a + (cx ² + (2c + d)x + d) exp(x) + 3e exp(3x)
y'' (part.) = (2cx + 2c + d) exp(x) + (cx ² + (2c + d)x + d) exp(x) + 9e exp(3x)
… = (cx ² + (4c + d)x + 2c + 2d) exp(x) + 9e exp(3x)
Substituting every relevant expression and simplifying reduces the equation to
(cx ² + (4c + d)x + 2c + 2d) exp(x) + 9e exp(3x)
… - 3 [a + (cx ² + (2c + d)x + d) exp(x) + 3e exp(3x)]
… +2 [(ax + b) + (cx ² + dx) exp(x) + e exp(3x)]
= 2x + (1 + 2x) exp(x) + 4 exp(3x)
… … …
2ax - 3a + 2b + (-2cx + 2c - d) exp(x) + 2e exp(3x)
= 2x + (1 + 2x) exp(x) + 4 exp(3x)
Then, equating coefficients of corresponding terms on both sides, we have the system of equations,
x : 2a = 2
1 : -3a + 2b = 0
exp(x) : 2c - d = 1
x exp(x) : -2c = 2
exp(3x) : 2e = 4
Solving the system gives
a = 1, b = 3/2, c = -1, d = -3, e = 2
Then the general solution to the DE is
y(x) = C₁ exp(2x) + C₂ exp(x) + x + 3/2 - (x ² + 3x) exp(x) + 2 exp(3x)
Pls if anyone knows the answer with work included/steps that will be greatly appreciated :) for 6 just want to know is it w y x or z
Answer:
Step-by-step explanation:
Let's begin calculating the MPH for Fran.: Joanne's MPH is 250 / 2.5 = 100 MPH.
Now I'm going to subtract the 100 MPH by Fran. going 10 MPH less: 100 - 10 = 90.
I can't see the bottom part of the graph, so based on the MPH, it might be X, if you could put a better picture it would be better!
Trish's punch recipe calls for 8 liters of lemon-lime soda and 4 liters of cranberry juice, Jenny's punch recipe requires 7
liters of lemon-lime soda and 6 liters of cranberry juice. Which recipe has a higher ratio of lemon-lime soda to cranberry
juice?
( A, neither, the ratios are equivalent
B. Trish's recipe
c. Jenny's recipe
D. not enough information
If sum of first 6 digits of AP is 36 and that of the first 16 terms is 255,then find the sum of first ten terms.
•Please answer it correctly ( step by step)
Answer:
100
Step-by-step explanation:
We have the sum of first n terms of an AP,
Sn = n/2 [2a+(n−1)d]
Given,
36= 6/2 [2a+(6−1)d]
12=2a+5d ---------(1)
256= 16/2 [2a+(16−1)d]
32=2a+15d ---------(2)
Subtracting, (1) from (2)
32−12=2a+15d−(2a+5d)
20=10d ⟹d=2
Substituting for d in (1),
12=2a+5(2)=2(a+5)
6=a+5 ⟹a=1
∴ The sum of first 10 terms of an AP,
S10 = 10/2 [2(1)+(10−1)2]
S10 =5[2+18]
S10 =100
This is the sum of the first 10 terms.
Hope it will help.
[tex]\sf\underline{\underline{Question:}}[/tex]
If sum of first 6 digits of AP is 36 and that of the first 16 terms is 255,then find the sum of first ten terms.
$\sf\underline{\underline{Solution:}}$
$\sf\bold\purple{||100||}$$\space$
$\sf\underline\bold\red{||Step-by-Step||}$
$\sf\bold{Given:}$
$\sf\bold{S6=36}$ $\sf\bold{S16=255}$$\space$
$\sf\bold{To\:find:}$
$\sf\bold{The \: sum\:of\:the\:first\:ten\:numbers}$$\space$
$\sf\bold{Formula\:we\:are\:using:}$
$\implies$ $\sf{ Sn=}$ $\sf\dfrac{N}{2}$ $\sf\small{[2a+(n-1)d]}$
$\space$
$\sf\bold{Substituting\:the\:values:}$
→ $\sf{S6=}$ $\sf\dfrac{6}{2}$ $\sf\small{[2a+(6-1)d]}$
→ $\sf{36 = 3[2a+(6-1)d]}$
→$\sf{12=[2a+5d]}$ $\sf\bold\purple{(First \: equation)}$
$\space$
$\sf\bold{Again,Substituting \: the\:values:}$
→ $\sf{S16}$ $\sf\dfrac{16}{2}$ $\sf\small{[2a+(16-1)d]}$
→ $\sf{255=8[2a + (16-1)d]}$
:: $\sf\dfrac{255}{8}$ $\sf\small{=31.89=32}$
→ $\sf{32=[2a+15d]}$ $\sf\bold\purple{(Second\:equation)}$
$\space$
$\sf\bold{Now,Solve \: equation \: 1 \:and \:2:}$
→ $\sf{10=20}$
→ $\sf{d=}$ $\sf\dfrac{20}{10}$ $\sf{=2}$
$\space$
$\sf\bold{Putting \: d=2\: in \:equation - 1:}$
→ $\sf{12=2a+5\times 2}$
→ $\sf{a = 1}$
$\space$
$\sf\bold{All\:of\:the\:above\:eq\: In \: S10\:formula:}$
$\mapsto$ $\sf{S10=}$ $\sf\dfrac{10}{2}$ $\sf\small{[2\times1+(10-1)d]}$
$\mapsto$ $\sf{5(2\times1+9\times2)}$
$\mapsto$ $\sf\bold\purple{5(2+18)=100}$
$\space$
$\sf\small\red{||Hence , the \: sum\: of \: the \: first\:10\: terms\: is\:100||}$
_____________________________
A sample of 13 sheets of cardstock is randomly selected and the following thicknesses are measured in millimeters. Give a point estimate for the population standard deviation. Round your answer to three decimal places. 1.96,1.81,1.97,1.83,1.87,1.84,1.85,1.94,1.96,1.81,1.86,1.95,1.89
===============================================
Explanation:
Add up the values to get
1.96+1.81+1.97+1.83+1.87+1.84+1.85+1.94+1.96+1.81+1.86+1.95+1.89= 24.54
Then divide over 13 (the number of values) to get 24.54/13 = 1.8876923 which is approximate.
So the mean is approximately 1.8876923
---------------------
Now make a spreadsheet as shown below
We have the first column as the x values, which are the original numbers your teacher provided. The second column is of the form (x-M)^2, where M is the mean we computed earlier. We subtract off the mean and square the result.
After we compute that column of (x-M)^2 values, we add them up to get what is shown in the highlighted yellow cell at the bottom of the column.
That sum is approximately 0.04403076924
Next, we divide that over n-1 = 13-1 = 12
0.04403076924 /12 = 0.00366923077
That is the sample variance. Apply the square root to this to get the sample standard deviation. This is the point estimate of the population standard deviation. As the name implies, it works for samples that estimate population parameters.
sqrt(0.00366923077) = 0.06057417576822
This rounds to 0.061 which is the final answer.
Factor the polynomial expression 3x4 + 24x.
Answer:
3x ( x+2)(x^2−2x+4)
Step-by-step explanation:
3x^4 + 24x.
Factor out the greatest common factor
3x*x^3 + 3x*8
3x(x^3+8)
Then factor the cubic term
The sum of cubes is a^3+b^3=(a+b)(a^2−ab+b^2)
3x ( x+2)(x^2−2x+4)
Mr. Cole packed 20 pounds into a suitcase, and Mrs. Cole packed 23 pounds into the same suitcase. They then had to remove 8 pounds because it was too heavy. How many pounds was their suitcase after making it lighter?
Answer:
35 lbs is the final weight
Step-by-step explanation:
20 +23 = 43 lbs
Then they had to remove 8 lbs
43 - 8 =35
35 lbs is the final weight
A control variable is:
A. Measured to show the effect of a change.
B. Kept the same to make an experiment a fair test.
C. Collected to draw conclusions.
D. Changed to test a hypothesis.
It’s in between a and b, they’re both technically true no?
Answer:
B: kept the same to make an experiment a faith test
solve for x : 2(x^2+9)-4=0
Answer:
no solution
Step-by-step explanation:
multiply 2 and get 2x^2+18-4=0
combine like terms
2x^2+14=0
subtract 14
2x^2=-14
there can't be a square root of a negative number so there's no solution
Answer:
x = ±i sqrt(7)
Step-by-step explanation:
2(x^2+9)-4=0
Add 4 to each side
2(x^2+9)-4+4=0+4
2(x^2+9)=4
Divide by 2
2(x^2+9)/2=4/2
(x^2+9)=2
Subtract 9 from each side
x^2 +9-9 = 2-9
x^2 = -7
Taking the square root of each side
sqrt(x^2) =sqrt(-7)
x = sqrt(-1 *7)
x = ±i sqrt(7)
Simplify the algebraic expression by combining like (or similar) terms.
2x−y2+3−3y2+2x+1
Answer:
-4y^2 + 4x +4
Step-by-step explanation:
add -y^2 and -3y^2 = -4y^2
add 2x + 2x = 4x
add 3+1 = 4
and then rearrange
Complete the remainder
Answer:
-14 is the answer for the second term (?)